Broncho-Hepatic-Fistula: A Complication of Rupture Liver Abscess - Rajbhandary, Gambhir Lal (Medical Journal of Shree Birendra Hospital, 2010)
DOI: 10.3126/mjsbh.v9i1.3489 Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 32-35